Pentingnya Posisi Budaya dan Efektivitas Organisasi dalam Kompetisi di Masa Depan - Semuil Tjiharjadi (Universitas Kristen Maranatha, 2007)
Cultures of organization have strong relationship with effectiveness of organization. Both of them can make great impact for the future of organization. In this journal, writer will show the culture research of three nations. There are Japan, South of Korea, and Indonesia. Many aspects of cultures have been found in multinationals companies that operations in Indonesia. All of them have similar situation of cultures and have to deal with it to make a good progress for effectiveness of company in competing with the future.